Effect of air exposure time on erodibility of intertidal mud flats - van Rees, Floris F.; Hanssen, Jill; Gamberoni, Stefano; Talmon, Arno M.; van Kessel, Thijs (Frontiers in Marine Science, 2024)
This study investigates the influence of air exposure time on the erodibility of intertidal mud flats, emphasizing the role of evaporation in altering sediment strength and cohesion. Through a comprehensive approach combining laboratory experiments, fieldwork, and numerical modelling, it explores the dynamic interactions between sediment properties and environmental conditions. The research reveals that drying significantly reduces sediment erodibility, with pronounced effects observed during the initial hours of air exposure. Laboratory tests demonstrate a direct correlation between drying time and increased yield stress for both artificial and field-derived mud samples. Field observations further support these results, showing spatial and temporal variations in water content and shear strength across various locations on a tidal flat. The study emphasizes the critical impact of mud content on water retention and the subsequent effect on sediment stability. The incorporation of drying time into erosion formulations within a numerical model highlights the importance of considering evaporation processes in predicting the morphological evolution of tidal flats. This research contributes to a better understanding of sediment transport dynamics in intertidal zones, offering insights into the mechanisms driving the growth and stability of mud flats. It underscores the necessity of integrating evaporation effects into cohesive sediment transport models to enhance the accuracy of predictions concerning the erosion and accretion of intertidal environments.